The Influence of Synthetic Analogues of PgF2 on the Evolution of Puerperal Period and the Duration of the Interval from Calving to the First Estrus in Cows - Nicolae Păcală; Casiana Șipețan; Ioan Bencsik; Dorel Dronca; Ada Cean; Ion Carabă; Marioara Nicula; Marinel Șipețan; Nenad Nedeljkovic; Cosmin Ganță (Scientific Papers Animal Science and Biotechnologies, 2023)
Puerperal period is the most critical period from the productive life of females, at the borderline between physiologic and pathologic. In this stage some reproductive turbulence may appear (uterine subinvolution, uterine infections, ovary inactivity, etc.), which may lead to the increase of the interval between calving and first estrus manifestation. The aim of our paper was to reduce the interval between calving and the firs estrus, also the reduction of the incidence of some impediments of the reproductive function in cows, after calving. For this purpose 500 mcg Cloprostenol were administered at different intervals from calving (12, 24, hours and 7 days). At experimental lots, the interval from calving to first estrus was, on average, 37.57 days, and at control lot it was 45.2 days. Regarding to the impairing of the reproductive function, uterine subinvolution, evaluated at 14 days from calving, it was 26.78% at experimental lots and 33.33% at control lot, and uterine infections were, on average, 14.8% at experimental lots and 16.2% at control lot. In conclusion, administration of synthetic analogues of PgF2, in the first week after calving, has a negative influence on puerperal period and interval from calving to first estrus manifestation.